1999
DOI: 10.1007/s002030050713
|View full text |Cite
|
Sign up to set email alerts
|

Thiamin biosynthesis in prokaryotes

Abstract: Twelve genes involved in thiamin biosynthesis in prokaryotes have been identified and overexpressed. Of these, six are required for the thiazole biosynthesis (thiFSGH, thil, and dxs), one is involved in the pyrimidine biosynthesis (thiC), one is required for the linking of the thiazole and the pyrimidine (thiE), and four are kinase genes (thiD, thiM, thiL, and pdxK). The specific reactions catalyzed by ThiEF, Dxs, ThiDM, ThiL, and PdxK have been reconstituted in vitro and ThiS thiocarboxylate has been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
267
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(271 citation statements)
references
References 35 publications
(36 reference statements)
3
267
0
1
Order By: Relevance
“…For clone 12, cof is most likely the gene responsible for resistance because cof is up-regulated in response to CF 3 -HMP. 2 In clones 13 and 14, either dxs or yajO could be the gene responsible for the observed antibiotic resistance. thiE is the cellular target for CF 3 -HMP, which explains the behavior of clone 15.…”
Section: Selection Of Clones Resistant To Bacimethrin or Cf 3 -Hmp-mentioning
confidence: 99%
“…For clone 12, cof is most likely the gene responsible for resistance because cof is up-regulated in response to CF 3 -HMP. 2 In clones 13 and 14, either dxs or yajO could be the gene responsible for the observed antibiotic resistance. thiE is the cellular target for CF 3 -HMP, which explains the behavior of clone 15.…”
Section: Selection Of Clones Resistant To Bacimethrin or Cf 3 -Hmp-mentioning
confidence: 99%
“…In E. coli, the thiazole moiety is formed from DXP (1-deoxy-D-xylulose-5-phosphate), tyrosine and cysteine [5][6][7][8][9]. Five gene products (ThiF, ThiS, ThiG, ThiH and ThiI) are involved in this step [10][11][12][13][14] (Figure 1). The pyrimidine unit is synthesized from AIR (5-aminoimidazole ribotide), and ThiC is re-quired for pyrimidine biosynthesis [14][15][16][17] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Five gene products (ThiF, ThiS, ThiG, ThiH and ThiI) are involved in this step [10][11][12][13][14] (Figure 1). The pyrimidine unit is synthesized from AIR (5-aminoimidazole ribotide), and ThiC is re-quired for pyrimidine biosynthesis [14][15][16][17] (Figure 1). Subsequently, ThiE, a thiamine phosphate synthase, couples the two ring structures of pyrimidine and thiazole to form TP [9,[17][18][19][20] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thiamine pyrophosphate (TPP), the biologically active cofactor, is generated by the condensation of two independently synthesized intermediates, 4-methyl-5-(␤-hydroxyethyl)thiazole (THZ) phosphate and 4-amino-5-hydroxymethyl-2-methylpyrimidine (HMP) pyrophosphate. In vivo labeling studies demonstrated that the carbon atoms in HMP were derived from the purine intermediate aminoimidazole ribonucleotide (AIR), although the biochemical details of this conversion have not been elucidated (2). Mutations causing an unconditional requirement for exogenous HMP or thiamine map to a single gene, thiC.…”
mentioning
confidence: 99%
“…Mutations causing an unconditional requirement for exogenous HMP or thiamine map to a single gene, thiC. In vivo labeling also determined the metabolic precursors to the THZ moiety, and several genes have been implicated in this synthesis (2,18). Our current understanding of the synthesis and salvage of TPP is presented in Fig.…”
mentioning
confidence: 99%